Peer review: The current landscape and future trends. Issue 1 (8th January 2016) - Jubb, Michael
Abstract: This paper is based on research commissioned by the Wellcome Trust in 2015 and catalogues current initiatives and trends in the systems and processes surrounding peer review. It considers issues such as open and interactive reviews, post‐publication comments and ratings, and the platforms provided by both publishers and other organisations to support such activity; third‐party peer review platforms; and measures from publishers and others to provide more recognition and rewards for peer reviewers. It also speculates on likely key trends in peer review for the future.